Strategi Pembelajaran Kewirausahaan Berbasis Proyek dalam Menumbuhkan Kemandirian dan Etos Kerja Islami Mahasiswa Psikologi Islam - Asfida Rahma; Mentari Marwa; Moh. Irmawan Jauhari (PT. Saha Kreasi Indonesia, 2025)
This study aims to describe the implementation of a project-based learning strategy in entrepreneurship courses to foster independence and Islamic work ethics among Islamic Psychology students. The background of this research stems from the need for a learning model that not only develops entrepreneurial competence but also integrates Islamic values into students’ work attitudes. This research employed a qualitative descriptive approach with the subjects of fifth-semester Islamic Psychology students enrolled in the Entrepreneurship course. Data were collected through classroom observations, interviews, and documentation of individual business plan projects, as well as an industrial visit to CV Nugraha Jaya, a small-medium enterprise producing various types of chips. The results indicate that project-based learning encourages students to be active, creative, and independent in designing applicable business ideas. Through contextual learning experiences in the field, students were able to connect entrepreneurial theories with real-world practice while internalizing Islamic work values such as honesty, discipline, responsibility, and diligence. This strategy not only enhances students’ entrepreneurial skills but also strengthens their Islamic character as future professionals with integrity. Therefore, the project-based learning strategy in entrepreneurship education can serve as an effective alternative to integrate intellectual, professional, and spiritual development within Islamic higher education institutions.